2021
DOI: 10.7577/hrer.4486
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the past: human rights education and epistemic justice

Abstract: Epistemic injustice in human rights education (HRE) can be found in a colonial historical trajectory of human rights that rests on accounts of western agency only. Such narratives overshadow the legacy of Indian and Pakistani freedom fighters and Latin American feminists who negotiated human rights against colonial, patriarchal and racist discourses after the Second World War. Without their contribution a United Nations (UN) rights concept risked being limited to a western trajectory of the ‘Rights of Man’ tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…The language of human rights might thus lead to new forms of exclusion, be it because some forms of human violation are not addressed by the languages of human rights, or because some violated people do not have equal access to these languages (Baxi, 2008). For this reason, myriad scholars call for a decolonial and more pluriversal form of human rights education (Adami, 2021;Becker, 2021;Williams & Bermeo, 2020;Zembylas, 2017). In the context of language teaching, it has also been suggested that the question of universality be discussed to ensure that cultural, linguistic and religious contexts are given due attention (Porto et al, 2018).…”
Section: Language Learning Through Human Rightsmentioning
confidence: 99%
“…The language of human rights might thus lead to new forms of exclusion, be it because some forms of human violation are not addressed by the languages of human rights, or because some violated people do not have equal access to these languages (Baxi, 2008). For this reason, myriad scholars call for a decolonial and more pluriversal form of human rights education (Adami, 2021;Becker, 2021;Williams & Bermeo, 2020;Zembylas, 2017). In the context of language teaching, it has also been suggested that the question of universality be discussed to ensure that cultural, linguistic and religious contexts are given due attention (Porto et al, 2018).…”
Section: Language Learning Through Human Rightsmentioning
confidence: 99%